2017
DOI: 10.21037/atm.2017.01.32
|View full text |Cite
|
Sign up to set email alerts
|

The first liquid biopsy test approved. Is it a new era of mutation testing for non-small cell lung cancer?

Abstract: Specific mutations in epidermal growth factor receptor (EGFR) gene are predictive for response to the EGFR tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer patients (NSCLC). According to international guidelines, the molecular testing in patients with advanced NSCLC of a non-squamous subtype is recommended. However, obtain a tissue sample could be challenging. Liquid biopsy allows to determine patients suitable for EGFR-targeted therapy by analysis of circulating-free tumor DNA (cfDNA) in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
170
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(174 citation statements)
references
References 39 publications
2
170
0
2
Order By: Relevance
“…cfDNA tracking is now being used as standard of care in the management of certain genotypes of NSCLC 15 . Since TP53 mutations are commonly found in both NSCLC 16,17 and SCLC 7,8,10 , we compared mutant AFs between these two types of lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…cfDNA tracking is now being used as standard of care in the management of certain genotypes of NSCLC 15 . Since TP53 mutations are commonly found in both NSCLC 16,17 and SCLC 7,8,10 , we compared mutant AFs between these two types of lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In June 2016, the U.S. Food and Drug Administration (FDA) authorized the cobas EGFR Mutation Test v2 (Roche Diagnostics, Indianapolis, IN) as the first liquid biopsy test to gain regulatory approval as a companion diagnostic to guide treatment choice. 34 This landmark decision was based on data from the ENSURE trial, which demonstrated the efficacy of erlotinib as compared with chemotherapy for first-line treatment in EGFR-mutated NSCLC. 35 Plasma EGFR mutations were shown in this study to be useful in identifying patients who benefited from erlotinib.…”
Section: Practical Applications Of Ctdna Analysismentioning
confidence: 99%
“…Recently, cell‐free DNA (cfDNA) has been widely studied as an alternative DNA source that can be used to detect EGFR mutation . cfDNA may be useful to genotype EGFR gene in newly diagnosed lung cancer patients with poor performance status of whom repeat biopsy is not possible . Moreover, cfDNA may also track impending appearances of EGFR T790M–resistant mutations that affect efficacy of first‐generation TKI .…”
Section: Introductionmentioning
confidence: 99%
“…6 cfDNA may be useful to genotype EGFR gene in newly diagnosed lung cancer patients with poor performance status of whom repeat biopsy is not possible. 7 Moreover, cfDNA may also track impending appearances of EGFR T790M-resistant mutations that affect efficacy of first-generation TKI. 8 Recently, osimertinib treatment shows promising results based on appearance of EGFR T790M mutations in cfDNA of patients previously treated with firstgeneration TKI.…”
Section: Introductionmentioning
confidence: 99%